Implementation of Full Day School in Character Building of Pancasila Student Profile in Elementary School - Fatimah Al Adawiyah; Ratnasari Diah Utami (Didaktika: Jurnal Kependidikan, 2024)
Education is actually an effort made by teachers to provide students to appreciate good values, and be able to apply them. Character education must be imparted from a young age, so that it develops itself will be a shared responsibility, both from parents in a home, teachers in schools and communities in the general environment. The purpose of this study is to determine how the introduction of full-day education shapes the character of Pancasila students in elementary school. Interviews, observation, and documentation are the strategies used to acquire data. The data validity test employs source and method triangulation approaches. The data analysis strategies employed in this study included data reduction, data display, and conclusion drafting. The results of the research conducted, namely the implementation of full day school for the formation of the student profile character of Pancasila at SDIT Al Kautsar Kebonduren obtained is starting from implementing character building and developing the value of the student profile of Pancasila in practical activities and applying directly.